Using the Zebrafish Lateral Line to Understand the Roles of Mitochondria in Sensorineural Hearing Loss - Holmgren, Melanie; Sheets, Lavinia (Frontiers in Cell and Developmental Biology, 2021)
Hair cells are the mechanosensory receptors of the inner ear and can be damaged by noise, aging, and ototoxic drugs. This damage often results in permanent sensorineural hearing loss. Hair cells have high energy demands and rely on mitochondria to produce ATP as well as contribute to intracellular calcium homeostasis. In addition to generating ATP, mitochondria produce reactive oxygen species (ROS), which can lead to oxidative stress, and regulate cell death pathways. Zebrafish lateral-line hair cells are structurally and functionally analogous to cochlear hair cells but are optically and pharmacologically accessible within an intact specimen, making the zebrafish a good model in which to study hair-cell mitochondrial activity. Moreover, the ease of genetic manipulation of zebrafish embryos allows for the study of mutations implicated in human deafness, as well as the generation of transgenic models to visualize mitochondrial calcium transients and mitochondrial activity in live organisms. Studies of the zebrafish lateral line have shown that variations in mitochondrial activity can predict hair-cell susceptibility to damage by aminoglycosides or noise exposure. In addition, antioxidants have been shown to protect against noise trauma and ototoxic drug induced hair-cell death. In this review, we discuss the tools and findings of recent investigations into zebrafish hair-cell mitochondria and their involvement in cellular processes, both under homeostatic conditions and in response to noise or ototoxic drugs. The zebrafish lateral line is a valuable model in which to study the roles of mitochondria in hair-cell pathologies and to develop therapeutic strategies to prevent sensorineural hearing loss in humans.